2017
DOI: 10.5194/amt-10-5063-2017
|View full text |Cite
|
Sign up to set email alerts
|

Improved methods for signal processing in measurements of mercury by Tekran<sup>®</sup> 2537A and 2537B instruments

Abstract: Abstract. Atmospheric Hg measurements are commonly carried out using Tekran ® Instruments Corporation's model 2537 Hg vapor analyzers, which employ gold amalgamation preconcentration sampling and detection by thermal desorption (TD) and atomic fluorescence spectrometry (AFS). A generally overlooked and poorly characterized source of analytical uncertainty in those measurements is the method by which the raw Hg atomic fluorescence (AF) signal is processed. Here I describe new software-based methods for processi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 22 publications
(25 reference statements)
1
31
0
Order By: Relevance
“…The DOHGS took part in the Reno Atmospheric Mercury Intercomparison eXperiment (RAMIX) whose results have been controversially discussed by Gustin et al (2013), Ambrose et al (2013) and Hynes et al (2017). According to Gustin et al (2013) and Ambrose et al (2013) GOM measurements by the DOHGS technique agreed well with nylon and cation exchange filters while yielding substantially higher values than the Tekran speciation system. Hynes et al (2017), on the other hand, found a good agreement of GOM concentrations measured by two-photon laser-induced fluorescence (2P-LIF) with and without a pyrolyzer (the 2P-LIF technique can measure GEM directly without using any filter) and by the Tekran speciation system.…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…The DOHGS took part in the Reno Atmospheric Mercury Intercomparison eXperiment (RAMIX) whose results have been controversially discussed by Gustin et al (2013), Ambrose et al (2013) and Hynes et al (2017). According to Gustin et al (2013) and Ambrose et al (2013) GOM measurements by the DOHGS technique agreed well with nylon and cation exchange filters while yielding substantially higher values than the Tekran speciation system. Hynes et al (2017), on the other hand, found a good agreement of GOM concentrations measured by two-photon laser-induced fluorescence (2P-LIF) with and without a pyrolyzer (the 2P-LIF technique can measure GEM directly without using any filter) and by the Tekran speciation system.…”
Section: Methodsmentioning
confidence: 98%
“…Despite an additional pump the nominal flow of 0.5 L (STP) min −1 could not be sustained at the highest flight levels. Limited air flow, the short sampling time and low concentrations resulted in only ∼ 2 pg of mercury, which is much smaller than 10 pg considered as minimum for biasfree internal default integration of the signal by the Tekran instrument (Swartzendruber et al, 2009;Slemr et al, 2016;Ambrose, 2017). For this reason, as previously mentioned, the raw analyzer signals were processed post-flight using a manual integration procedure described in detail by Slemr et al (2016).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations